THE BUDGET DEFICIT IMPACT ON THE MATERIAL AND TECHNICAL SUPPORT OF UKRAINE’S HEALTHCARE INSTITUTIONS - Petryna, M.Yu; Muratova , M.I.; Kushlyk , O.Yu; Kochkodan , V.B. (The actual problems of regional economy development, 2022)
The article is devoted to the study of the impact of the budget deficit on the logistics of health care facilities in Ukraine. It is substantiated that Ukraine lags far behind its European neighbors in such indicators as life expectancy and mortality. The main preconditions for high mortality are risk factors such as smoking, overweight, lack of exercise and excessive alcohol consumption, along with unresolved issues related to the spread of infectious diseases and high levels of injuries. Ukraine spends much of its GDP on health care, but its per capita GDP in Ukraine is lower than in most European countries. At the same time, many countries are achieving fairly good life expectancy and mortality rates at a comparable cost of health. Ukraine’s health care system is cumbersome and outdated and is based on a model with strict management and funding procedures. This situation is due to deep shortcomings in the national health care system due to lack of modernization, ignoring the needs of the population, failure to use modern world trends, inefficient operation of the system and high levels of corruption. Analysis of the state of logistics on the results of this work showed that the vast majority of health care facilities are not equipped with equipment for diagnosis or were provided with such equipment in 1990-2000. From this we can conclude that the existing equipment is obsolete and physically worn out. Therefore, it was decided to replace the equipment that has been in operation for more than 10 years. The necessary additional amount of equipment to meet the needs of health care support institutions of Ukraine in terms of administrative-territorial units has been identified. The use of computed tomography, radiography and ultrasound, and ventilators for lung treatment was analyzed to confirm the presence of acute respiratory disease COVID-19 caused by SARS-CoV-2 virus. Thanks to the coordinated cooperation of the involved central executive bodies and local self-government bodies, outstanding results were achieved in equipping 256 health care institutions throughout Ukraine with the latest modern equipment. Evaluating the performance indicators, the article proves that currently about 20% of the available material and technical base has been updated.